Chapter Sentinel-2 e campionamenti in situ per il monitoraggio delle acque marine dell'Abruzzo: primi risultati - Scamosci, Emanuela (Proceedings e report, 2020)
In this study, the estimate of chlorophyll "a" and the dispersion of sediment in the sea, calculated from Sentinel-2, was compared with real data acquired in situ by a multiparametric probe, along the Abruzzo coast. The ultimate goal is to optimize parameters and algorithms to be able to derive concentration maps of chlorophyll and suspended solids from satellite, taking advantage of the high time frequency and high spatial resolution of the detections. This information is of particular relevance for aquaculture activities, for monitoring water quality and for analyzing sedimentary processes.